Study of Naidid worms community associated with two species of aquatic plants in River Tigris inside Baghdad City / Iraq (Baghdad Science Journal, 2014)
The present study is concern with the interaction between the naidid worms diversity and the species of aquatic plant within which the worms found . For this purpose, two species of aquatic plant were used, Ceratophyllum demersum and Eichhornia crassipes. 12 samples of aquatic plants were collected , as one sample monthly for a period from September 2012 to September 2013 from different site on Tigris river within Baghdad City.From C. demersum, 1428 individuals, were sorted during the study period, related to 17 species. 12 species of subfamily Naidinae which are Chaetogaster limnaei , C. diastrophus , Ophidonais serpentine , Dero ( Dero) digitata. , D.(D.) evelinae , Nais pseudobtosa , N.simplex, N.stolci , N.Paradalis , N.elingius , N. variabilis and N. communis. In addition to five species of subfamily Pristininae, two species of Pristina , which are P. longiseta and . P. aequiseta, and three species of pristinella, which are P. . Jenkinae , P. sima , and P. osborni. Dero ( Dero) digitata was recorded the higher number of 430 individuals,with a percentage of 28.11% of the total sorted worms.About the aquatic plant Eichhornia crassipes, a total of 829 worms were sorted from it, which are related to six species of Naidinae , which are diaphanous , Ophidonais serpentine, Stylaria lacustris , Slavina appendiculata , N. variabilis and finally the species Allonais inaequalis. There was no any species of Pristininae sorted from this plant. The highest number of 467 individuals was recorded by the species Slavina appendiculata, with a percentage of 52.3% of the total number and 228 individual with a percentage of 25.5% was recorded by Allonais inaequalis.